Physics Oseanography Around Artificial Reef On The Pantai Of Damas, Trenggalek District, East Java - Maulana Fikri; Andik Isdianto; Oktiyas Muzaky Luthfi (Universitas Airlangga, 2021)
Damage to coral reefs is generally caused by destructive fishing activities, they were the usega of explosives, cyanide toxic materials, coral mining for building materials, anchor boat anchors, and the results of sedimentation. Efforts to speed up the process of coral reef recovery, several methods of rehabilitation that can be done include coral transplantation and sinking of artificial reefs. The artificial reef is an alternative to reduce the pressure caused by fishing and destruction of natural coral reefs through the creation of new productive fishing grounds. The purpose of this study was to determine the relationship of water parameters (physical oceanography) for biota around artificial reefs based on Geographic Information Systems. The results of identification of oceanographic parameters in the waters of Damas Beach, Trenggalek Regency consist of: (a). depths range from 0-45 meters, (b). brightness ranges from 2 - 6 meters, (c). water temperature ranges from 25.18-29.59ºC, (d). water turbidity ranges from 0.3-4.32 NTU, (e). type of substrate base waters of Damas Beach fine black sand, (f). current speed ranges from 0.1-0.4 m/s, (h). the average wave height of Damas Beach in the morning, afternoon and evening is 5.6 cm, 8.14 cm and 6.2 cm, (i). the total suspended solid waters of Damas Beach range from 35-351 mg/L. The physical oceanographic parameters are still safe for the growth and development of biota in the waters of Damas Beach, Trenggalek Regency.